Transitional analysis for multi-objective operative improvement of reformate quality and hydrogen production from a naphtha catalytic reforming process - F. Velázquez-Alonso; C.A. González-Ramírez; J.R. Villagómez-Ibarra; E.M. Otazo-Sánchez; M. Hernández-Juárez; F. Pérez-Villaseñor; A. Castro-Agüero; L.O. Alemán-Vázquez (Heliyon)
The hydrogen produced (H2) in the Catalytic Naphtha Reforming (CNR) is important in quantity and quality, for the feedback of the process and for supplying the hydrotreatment processes in current refineries. In this work it is presented a study by process simulation using Aspen HYSYS® for finding operative transitional modes that simultaneously improve quality of the reformate and hydrogen production of the CNR. The operative conditions that were studied correspond to the recirculation ratio of hydrogen/hydrocarbon (H2/HC), with values between 2 and 6, and the temperature (T), between 450 and 525 °C, in order to determining the best operative transitional route from the initial operative state to a local improved state, applying the method of superposition of response surfaces and criteria assessment of improvement in quality and quantity of hydrogen produced. A numerical multi-objective operative improvement analysis was performed resulting the objective variables as: Research Octane Number (RON) = 90.72, mass fraction of H2 produced (%m of H2) = 2.9, quality of recycled H2 (yH2)R = 0.87, and quality of produced hydrogen (yH2)S = 0.9653. Experimental pilot plant data and full-scale industrial data were compared with simulations observing significant similitudes.